2010
DOI: 10.1590/s0102-86502010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Successful transplant of mesenchymal stem cells in induced osteonecrosis of the ovine femoral head: preliminary results

Abstract: PURPOSE: Evaluate the bone tissue recovery following transplantation of ovine mesenchymal stem cells (MSC) from bone marrow and human immature dental-pulp stem cells (hIDPSC) in ovine model of induced osteonecrosis of femoral head (ONFH). METHODS: Eight sheep were divided in three experimental groups. First group was composed by four animals with ONFH induced by ethanol through central decompression (CD), for control group without any treatment. The second and third group were compose by two animals, six weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 28 publications
0
46
0
1
Order By: Relevance
“…The first protocol, drawn up according to Feitosa 23 (bone marrow of sheep), was ineffective since it did not enable cell adherence and viability. The second protocol, based on methods used by Fuchs et al 14 showed formation of a halo of white and red blood cell supernatants that persisted even after washing the material.…”
Section: Discussionmentioning
confidence: 99%
“…The first protocol, drawn up according to Feitosa 23 (bone marrow of sheep), was ineffective since it did not enable cell adherence and viability. The second protocol, based on methods used by Fuchs et al 14 showed formation of a halo of white and red blood cell supernatants that persisted even after washing the material.…”
Section: Discussionmentioning
confidence: 99%
“…Uma nova opção para reparar grandes falhas ósseas seria o emprego de um compósito constituído pela associação de materiais biocompatíveis biológico (tecido ósseo heterólogo) e sintético (polimetilmetacrilato), com propriedades osteogênicas, osteoindutoras e osteocondutoras, que não favorecesse infecção nem a colonização bacteriana, que proporcionasse sustentação mecânica, que fosse biomodelado, de fácil aquisição e baixo custo, que não necessitasse de meio especializado para sua preservação, que preenchesse completamente a falha óssea, eliminando, com isso, problemas inerentes ao enxerto autógeno (Friedlaender 1982, Khan 2000, Alievi et al 2007, Feitosa et al 2010, Turrer & Ferreira, 2008, 2013a.…”
unclassified
“…In the initial stage of ONFH, core decompression, together with allogeneic fibula rod support, is considered an effective surgical intervention. However, However, this treatment retains the femoral head in only 60-80% of cases in the short and medium term (12) . Femoral head core decompression involves drilling a tunnel to reduce the pressure on the femoral head, thereby alleviating pain.…”
Section: Discussionmentioning
confidence: 99%